2008
DOI: 10.2186/prp.7.78
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Relationship between Subjective Oral Dryness and Stimulated Saliva or Oral Mucosal Moisture

Abstract: Clinical significanceThis study investigated the relationship between subjective oral dryness and stimulated saliva or oral mucosal moisture. Both stimulated saliva and oral mucosal moisture are related to subjective oral dryness, and the Saxon test and the test using an oral moisture checking device are useful for assessing subjective oral dryness. AbstractPurpose: The present study aimed to investigate the relationship between subjective oral dryness and stimulated saliva or oral moisture. Methods: Twenty-on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 17 publications
(14 reference statements)
0
13
0
Order By: Relevance
“…showed a positive correlation between saliva wetness and unstimulated salivary flow rate as measured by the spitting method in tube‐fed patients. In addition, the relationship between the results of moisture measurements and symptoms of dry mouth are reportedly correlated. Takahashi et al .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…showed a positive correlation between saliva wetness and unstimulated salivary flow rate as measured by the spitting method in tube‐fed patients. In addition, the relationship between the results of moisture measurements and symptoms of dry mouth are reportedly correlated. Takahashi et al .…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the moisture level had a significantly positive correlation with saliva wetness. There is no previous information on this relationship; however, it is reported that each result of moisture measurement corresponds to that of conventional methods. Using a moisture‐checking device, Takahashi et al .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations